If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(a + -7) + 8 = 2(a + -4) Reorder the terms: 4(-7 + a) + 8 = 2(a + -4) (-7 * 4 + a * 4) + 8 = 2(a + -4) (-28 + 4a) + 8 = 2(a + -4) Reorder the terms: -28 + 8 + 4a = 2(a + -4) Combine like terms: -28 + 8 = -20 -20 + 4a = 2(a + -4) Reorder the terms: -20 + 4a = 2(-4 + a) -20 + 4a = (-4 * 2 + a * 2) -20 + 4a = (-8 + 2a) Solving -20 + 4a = -8 + 2a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-2a' to each side of the equation. -20 + 4a + -2a = -8 + 2a + -2a Combine like terms: 4a + -2a = 2a -20 + 2a = -8 + 2a + -2a Combine like terms: 2a + -2a = 0 -20 + 2a = -8 + 0 -20 + 2a = -8 Add '20' to each side of the equation. -20 + 20 + 2a = -8 + 20 Combine like terms: -20 + 20 = 0 0 + 2a = -8 + 20 2a = -8 + 20 Combine like terms: -8 + 20 = 12 2a = 12 Divide each side by '2'. a = 6 Simplifying a = 6
| -6p+4p=4(1+2p)-8(2p+5) | | 4x+5x=6x | | 0.9x-0.5(5-x)=6.6 | | X(3x)=486 | | 4x+7=-30 | | -7+8=3 | | 9x+4=2x+32 | | 0.015w-1.85=1.615 | | -4(2t+8)=-8 | | -2(-7n-8)-8n=6(n-6) | | 8z+4-5z=44-5 | | 12x-2(6x-10)=1 | | g(x)=x-25x^3 | | x+36-12=42 | | 4y-12=2x | | -5(v+1)+5(1-7v)=4v+4v | | 8z+4+5z=44-5z | | -2(7n-8)-8n=6(n-6) | | -1x-7=18 | | 3(x^2+4x-1)=0 | | -20+2y=-22 | | 18+2x-12=42 | | 4(f-3)=-4 | | 2(y-1)+y=37 | | -6+14x=36 | | 10(s-6)=-129 | | 8x-24=5x+57 | | 0=x-25x^2 | | -(c-9)=-2 | | -5(5a+4)=55 | | =-x-5x-2 | | x=-16t^2+900 |